Comparison of the length of shoulder girdle’s muscles, neck and shoulder range of motion in patients with chronic neck - shoulder pain and healthy subjects - A Moezy (مجله دانشگاه علوم پزشکی گرگان, 2017)
Background and Objective: One of the most common musculoskeletal injuries in modern societies is neck and shoulder pains which often lead to postural disorders and soft tissue shortenings. This study was done to compare the length of shoulder girdle’s muscles in healthy subjects and patients with shoulder and neck pain.